The Existence of an Integrated Law Enforcement Center in the Settlement of General Election Crimes at the General Election Supervisory Agency - Supusepa, Melky Iron; Toule, Elsa Rina Maya; Supusepa, Reimon (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The existence of Gakkumdu as an integrated law enforcement center has an important role in handling election crimes which aims to equlize understanding of the handling of election crime violations by Bawaslu, the Police and the Prosecutor’s office. The presence of Gakkumdu as a manifestation of judicial power which is given attribution authority by Law Number 7 07 2017 cncerning Election is a bright spot for legal certainly regarding the handling of criminal election violations; however, Gakkumdu’s authority is not yet completely independent in handling election criminal violations because it it still tied to the respective agencies of origin so that sectoral subjectivity and ego can sometimes influence decision regarding handling election criminal violations.Purposes of the Research: Examining and explaining the existence of the Integrated Law Enforcement Center (Gakkumdu) in resolving election crimes in the Tanimbar Islands Regency and reviewing and explaining the factors that influence the resolution of election crimes in the Tanimbar Islands Regency by the Integrated Law Enforcement Center (Gakkumdu).Methods of the Research: The Research method used is empirical legal research. Research approaches are a case approach, a statutory approach and a conceptual approach. The sources of legal materials used are primary legal materials and secondary legal materials. Techniques for collecting legal materials through documentation studies and field research and then analyzed through persepective using qualitative methods.Results Main Findings of the Research: The expected result I that when talking about alleged criminal election violations, that hope is in the hands of the Gakkumdu Center, the election supervisory institution only as an entry point, the analysis and subsequent decisions rest on the shoulders of the Gakkumdu center (Election supervisor, Police and Prosecutor’s Office) and on their shoulders. Hopefully there is still a glimmer of hope for the enforcement of election crimes in Indonesia.